2017
DOI: 10.18632/oncotarget.19370
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis showing that ERCC1 polymorphism is predictive of osteosarcoma prognosis

Abstract: To investigate correlations between excision repair cross-complementation group 1 (ERCC1) and 2 (ERCC2) polymorphisms and osteosarcoma prognosis, we conducted a meta-analysis of studies published through October 2016. Studies were identified in the PubMed, ScienceDirect, Springer, and Web of Science databases using preferred reporting items for systematic reviews and meta-analyses (PRISMA). Odds ratios (ORs) or hazard ratios (HRs) and their 95% confidence intervals (CIs) for overall survival (OS), tumor respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…An investigation carried out by Liu et al revealed the fact that ERCC1 -rs11615 is likely to be a useful genetic marker for the prediction of the osteosarcoma prognosis and that the CC genotype is correlated with a better clinical outcome. 46 The work performed by Liu et al indicated that the XRCC1- 399A/A genotype was significantly correlated with a better clinical outcome. 47 Previous studies demonstrated that genetic variants of ERCC2 and ERCC5 may be the independent prognostic factors in the patients with melanoma 32 , 48 and osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation carried out by Liu et al revealed the fact that ERCC1 -rs11615 is likely to be a useful genetic marker for the prediction of the osteosarcoma prognosis and that the CC genotype is correlated with a better clinical outcome. 46 The work performed by Liu et al indicated that the XRCC1- 399A/A genotype was significantly correlated with a better clinical outcome. 47 Previous studies demonstrated that genetic variants of ERCC2 and ERCC5 may be the independent prognostic factors in the patients with melanoma 32 , 48 and osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the potential predictive and prognostic role of ERCC1 (C118T and C8092A) and ERCC2 (A751C and G312A) genetic polymorphisms on either tumors’ response to cisplatin chemotherapy or clinical outcomes [ 14 , 17 , 19 – 23 ]. Of these studies, many have shown significant associations with some of these variants, but others still revealed contradictory outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Excision repair cross-complementing 1 (ERCC1) and excision repair cross-complementing 2 (ERCC2) are major members in NER pathway [ 16 ]. Many single nucleotide polymorphisms have been identified in ERCC1 and ERCC2 genes; of these polymorphisms, ERCC1 (C118T & C8092A) and ERCC2 (A751C & G312A) have been shown to affect the repair capacity and concomitantly the tumor’s sensitivity to cisplatin [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning DNA repair, the most consistent data have been reported for polymorphisms of the excision repair 1 (ERCC1) and excision repair 2 (ERCC2) genes, both involved in the nucleotide excision repair (NER) pathway. Although findings have sometimes been contradictory, two meta-analyses indicated that HGOS patients carrying the C allele of ERCC1 rs11615 [16,17] or the A allele of ERCC2 rs1799793 [17] have higher probabilities of responding to conventional chemotherapy among Chinese populations. Among genes related to methotrexate metabolism, the most widely studied in HGOS has been the 5,10-methylenetetrahydrofolate reductase (MTHFR) [15,18].…”
Section: Candidate Predictive and Prognostic Biomarkersmentioning
confidence: 99%